THE COMPLETENESS, BREADTH AND DEPTH : A COMPARISON BETWEEN INDONESIAN AND CAMBRIDGE HIGH SCHOOL BIOLOGY TEXTBOOKS FOR CIRCULATORY SYSTEM - Dahlia Gultom; Syarifuddin Syarifuddin (Universitas Negeri Medan, 2016)
This study was aimed to compare the completeness, breadth and depth high school biology textbook of Indonesia and Cambridge publisher. The comparison use an instrument based on National Education Standard Agency ( BSNP ) assesment instrument for book evaluation. The topic that compared in this research is Circulatory system. The sample was taken with purposive sampling method. The biology textbook from Indonesian published by Erlangga, Esis and BSE. One Cambridge book’s publisher that is used in several schools, like Singapore, Malaysia, United Kingdom and Indonesia. The result data quantitative showed that the score of textbooks on a sample based on the completeness aspect of Cambridge book’s publisher has score 4 or 100 % , Erlangga book’s publisher has score 4 or 100 %, Esis book’s publisher has score 4 or 100 %, and BSE publisher has score 4 or 100 %. For the breadth aspect score of textbooks are Cambridge book’s publisher has score 4 or 100 %, Erlangga book’s publisher has score 4 or 90 %, Esis book’s publisher has score 4 or 100 %, and BSE publisher has score 4 or 100 %. In the depth aspect score of textbooks are Cambridge book’s publisher has score 4 or 87.5 %, Erlangga book’s publisher has score 4 or 100 %, Esis book’s publisher has score 4 or 100 and BSE publisher has score 4 or 100 %. Hence, can be concluded that all textbooks that had been analyzed have content feasibility with each syllabus.Keywords: Completeness, Breadth, Depth, Textbook, Circulatory System